2019
DOI: 10.1016/j.bj.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Repair bond strength of composite to Er,Cr:YSGG laser irradiated zirconia and porcelain surfaces

Abstract: Background Fracture or chipping are major concerning failures of an all-ceramic restoration. Repairing of the failure restoration using intra-oral technique is time saving and cost effective treatment modality. The present study was proposed to evaluate effect of Er,Cr:YSGG laser irradiation on shear bond strength between zirconia/porcelain and composite resin. Methods Thirty zirconia and thirty zirconia based porcelain disc shape specimens were prepared. Three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Laser showed the statistically significantly lowest mean shear bond strength, which is in accordance with Saraç et al [15]. This can be explained as the porcelain has high content of silica 50-60% by weight and the action of Cojet increased the amount of silica by embedding silica coated aluminum oxide to the surface of the porcelain which resulted in high amount of chemically bondable silica that achieved high bond strength to the silane coupling agent and also can be attributed to the increase in surface area and roughness that resulted from the blasting action of silica coated aluminum oxide to the surface of porcelain which was considered by Saraç et al the "major" factor for a strong bond [17,19] In general the laser shear bond strength values were less in the porcelain sub groups than in zirconia sub groups and this can be explained in accordance to Sari et al [22] in his study that measured light transmission of Er:Yag laser through different ceramic materials and it was found that the light transmission of laser in monolithic zirconia is higher than in porcelain which means the energy of the laser is not absorbed in zirconia with the same degree in feldpsathic porcelain and as a result it will not affect the surface or change its topography as well as the feldpsathic porcelain surface [22][23][24][25][26][27][28].…”
Section: Regarding the Effect Of Ceramic Typesupporting
confidence: 70%
“…Laser showed the statistically significantly lowest mean shear bond strength, which is in accordance with Saraç et al [15]. This can be explained as the porcelain has high content of silica 50-60% by weight and the action of Cojet increased the amount of silica by embedding silica coated aluminum oxide to the surface of the porcelain which resulted in high amount of chemically bondable silica that achieved high bond strength to the silane coupling agent and also can be attributed to the increase in surface area and roughness that resulted from the blasting action of silica coated aluminum oxide to the surface of porcelain which was considered by Saraç et al the "major" factor for a strong bond [17,19] In general the laser shear bond strength values were less in the porcelain sub groups than in zirconia sub groups and this can be explained in accordance to Sari et al [22] in his study that measured light transmission of Er:Yag laser through different ceramic materials and it was found that the light transmission of laser in monolithic zirconia is higher than in porcelain which means the energy of the laser is not absorbed in zirconia with the same degree in feldpsathic porcelain and as a result it will not affect the surface or change its topography as well as the feldpsathic porcelain surface [22][23][24][25][26][27][28].…”
Section: Regarding the Effect Of Ceramic Typesupporting
confidence: 70%
“…Zirconia-based restorations (ZBR) have been widely used in dentistry due to their superior mechanical properties and excellent aesthetics [1]. Zirconia has a fracture toughness of 7-19 MPa m 1/2 and flexural strength of 1200 MPa, therefore it could act as a durable framework for dental restorations [2]. ZBR has an opaque zirconia substructure which is traditionally veneered by tooth-coloured glass-ceramics [3].…”
Section: Introductionmentioning
confidence: 99%
“… 16 17 18 It has also been determined that using erbium, chromium: yttrium-scandium-gallium-garnet (Er,Cr: YSGG) laser irradiation enhances the bond strength of restorative materials by creating micro-retentive areas. 19 20 …”
Section: Introductionmentioning
confidence: 99%